(untitled) (Research, Society and Development, 2022)
Early mobilization (PM) consists of therapeutic procedures that assist in the physical recovery of patients kept in an intensive care unit (ICU). The objective of this study was to demonstrate the importance of PM in reducing the length of stay of patients in the ICU. The present study consists of an integrative review of the scientific literature carried out through publications made available in articles, books and dissertations in the online database, Scielo, Medline/Pubmed and the Virtual Health Library. The keywords used were early mobilization, ICU, physical therapy and critically ill patients, in Portuguese and English. The analyzed results demonstrate that MP is effective in several clinical situations. Muscle strengthening, reduced length of stay in the ICU and the risk of hospital infection, in addition to optimizing financial resources were the main positive effects related to PM. However, very early PM can have negative effects, and PM application is recommended within 72 hours of patient admission to the ICU. The introduction of PM protocols is extremely important and relevant for the recovery and reduction of the length of stay of patients hospitalized in intensive care units.